Optimizing Work Efficiency by Addressing Operator Fatigue Concerns: Mengoptimalkan Efisiensi Kerja dengan Mengatasi Masalah Kelelahan Operator - Agil, Mochamad Sofwan; Isma Putra, Boy (Indonesian Journal of Innovation Studies, 2024)
The study conducted at PT. Tjiwi Kimia aimed to assess the fatigue criteria and mental load experienced by production operators of cartoon box in the context of the company’s 3-shift operation. Using the Bourdon Wiersma method for fatigue evaluation and the NASA TLX method for mental load analysis, findings revealed varying levels of fatigue and mental burden across different shifts. Notably, the morning shift exhibited "Good enough" speed fatigue but "Doubtful" accuracy fatigue, while the night shift showed "Enough" consistency fatigue. Furthermore, the mental burden was highest during the night shift, categorized as "High." These findings underscore the importance of addressing shift-related fatigue and mental load in industrial settings. Recommendations for implementing 3-shift rotations with weekends off and providing short breaks reflect potential strategies to mitigate worker fatigue and improve overall well-being. Future research could explore additional factors influencing worker fatigue and mental load, such as ergonomic interventions or technological advancements in production processes. Highlight: Shift Work Effects: Assessing fatigue and mental load in industrial settings. Evaluation Methods: Bourdon Wiersma and NASA TLX for worker analysis. Improvement Suggestions: Implementing 3-shift rotations and providing breaks. Keywoard: Fatigue, Mental Load, Production Operators, Shift Work, Industrial Setting